Co-inoculação de Rhizobium tropici e Azospirillum brasilense em feijoeiro cultivado sob duas lâminas de irrigação: produção e qualidade fisiológica de sementes - Peres, Amanda Ribeiro [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The average yield of beans in Brazil is low. Alternatives that can increase yield in a sustainable manner should be preconized, such as reducing the use of nitrogen fertilizers through the adoption of biological nitrogen fixation. In this scenario, an alternative technique of co-inoculation or also called the mixed inoculation with symbiotic and non-symbiotic bacteria has been studied in leguminous, however there are few studies in field with common bean under the influence of the amount of water irrigated. Thus the objetive of this study was to evaluate the efficiency of inoculation and co-inoculation of common bean with Rhizobium tropici and Azospirillum brasilense under two irrigation depths on production and physiological seed quality. The experiment was performed in the fall/winter of the years 2012 and 2013, in Selviria-MS. A randomized block design in a 5x2 factorial scheme with four repetitions was used. The treatments were constituted by the combination of five forms of nitrogen supply (control non-inoculated with 40 kg ha- 1 of nitrogen in topdressing; control non-inoculated with 80 kg ha- 1 of N in topdressing; A. brasilense inoculation with 40 kg ha-1 of N in topdressing; R. tropici inoculation with 40 kg ha-1 of N in topdressing; and co-inoculation of A. brasilense and R. tropici with 40 kg ha- 1 of N in topdressing) and two irrigation depths (recommended and 75% of the recommended). Was concluded that the co-inoculation, the inoculation of R. tropici, the inoculation of A. brasilense associated with 40 kg ha-1 of nitrogen in topdressing and the control non-inoculation with application of 80 kg ha-1 of N topdressing not increase of grain yield compared to control non-inoculation with 40 kg ha-1 of nitrogen in topdressing. Considering the development conditions of the experiment, the use of 75% of the recommended irrigation depth provides similar or greater grain yield than the ...

A produtividade média de feijão no Brasil é baixa. Alternativas que possam aumentar a produtividade de forma sustentável devem ser preconizadas, tais como a redução do uso de fertilizantes nitrogenados pela adoção da fixação biológica de nitrogênio. Neste cenário, uma técnica alternativa de co-inoculação ou também denominada de inoculação mista com bactérias simbióticas e assimbióticas tem sido estudada em leguminosas, no entanto existem poucos estudos em campo com feijoeiro e sobre a influência da quantidade de água irrigada. Dessa forma, o objetivo deste trabalho foi avaliar a eficiência da inoculação e co-inoculação de feijão com Rhizobium tropici e Azospirillum brasilense sob duas lâminas de irrigação na produção e qualidade fisiológica de sementes. O experimento foi desenvolvido no período de outono/inverno dos anos de 2012 e 2013, no município de Selvíria-MS. O delineamento experimental foi de blocos casualizados em esquema fatorial 5x2, com quatro repetições. Os tratamentos foram constituídos pela combinação de cinco formas de fornecimento de nitrogênio (testemunha sem inoculação com 40 kg ha-1 de nitrogênio em cobertura; testemunha sem inoculação com 80 kg ha-1 de N em cobertura; inoculação de A. brasilense com 40 kg ha-1 de N em cobertura; inoculação de R. tropici com 40 kg ha-1 de N em cobertura; e co-inoculação de A. brasilense e R. tropici com 40 kg ha-1 de N em cobertura) e duas lâminas irrigação (recomendada e 75% da recomendada). A aplicação de nitrogênio em cobertura foi realizada utilizando a ureia. Concluiu-se que a co-inoculação, a inoculação de R. tropici, a inoculação de A. brasilense associadas a 40 kg ha-1 de nitrogênio em cobertura e a testemunha sem inoculação com aplicação de 80 kg ha-1 de N em cobertura não proporcionam acréscimos de produtividade em relação a testemunha não inoculada com 40 kg ha-1 ...
Keywords: Feijão comum; Nitrogenio na agricultura; Azospirillum brasilense; Sementes - Fisiologia; Agua de irrigação; Feijão - Inoculação; Inoculation